1994
DOI: 10.1002/jmv.1890440305
|View full text |Cite
|
Sign up to set email alerts
|

Human rotavirus subgroups and serotypes in children with acute gastroenteritis in Saudi Arabia from 1988 to 1992

Abstract: Rotavirus infection was detected in 524 (42.2%) of the 1,242 stool specimens collected from infants and young children with acute gastroenteritis admitted to a major pediatric hospital in Jeddah, Saudi Arabia, between March 1988 and December 1992. Enzyme-linked immunosorbent assay (ELISA) and monoclonal antibodies specific for subgroup I and II were used to examine 80 rotavirus positive specimens. Subgroup I was detected in 21 (26.3%) and subgroup II in 49 (61.3%) specimens. Six specimens reacted with both sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…In other studies in which samples were collected in one hospital in Australia, G I predominated for 10 years (1980-1989) (12). In Saudi Arabia (39) and Italy (4), G1 was the most commonly detected serotype for five consecutive years, and a study in Estonia revealed that G1 was predominant for four successive seasons (21). Thus, the predominance of the G1 serotype for several successive seasons was a common observation from the global perspective.…”
Section: Discussionmentioning
confidence: 97%
“…In other studies in which samples were collected in one hospital in Australia, G I predominated for 10 years (1980-1989) (12). In Saudi Arabia (39) and Italy (4), G1 was the most commonly detected serotype for five consecutive years, and a study in Estonia revealed that G1 was predominant for four successive seasons (21). Thus, the predominance of the G1 serotype for several successive seasons was a common observation from the global perspective.…”
Section: Discussionmentioning
confidence: 97%
“…The analysis of rotavirus incidence in different settings showed that 23.8% of samples were rotavirus-positive in hospitalized children. Mohammed et al (1994) found an overall rotavirus prevalence rate of 42.2% in Saudi Arabia, while in Brazil, prevalence rates ranged from 13 to 20% in different states (Pereira et al 1993). Children from outpatient clinics showed only 2.7% of rotavirus-positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…Subgrouping enzyme-linked immunosorbent assays (ELISAs) have been used extensively in epidemiological studies. The rotaviruses most commonly found in humans belong to SG II (2,4,8,14,19), while SG I is common among animal rotaviruses (18,23).Previous studies have mapped SG I specificity to amino acid (aa) position 305 and the region between positions 296 and 299 and SG II specificity to residue 315 (18, 23). It is still unclear whether SG specificity is determined by linear or conformational epitopes, although there is some evidence that the epitopes recognized by SG-specific MAbs are conformational and are present only in the trimeric form of VP6 (9).…”
mentioning
confidence: 99%
“…Subgrouping enzyme-linked immunosorbent assays (ELISAs) have been used extensively in epidemiological studies. The rotaviruses most commonly found in humans belong to SG II (2,4,8,14,19), while SG I is common among animal rotaviruses (18,23).…”
mentioning
confidence: 99%